Análise de fatores que influenciam aspectos financeiros de implantação e operação de usinas de reciclagem de RCD - Moresco, Joana Michelon (Universidade do Vale do Rio dos Sinos, 2016)
Construction and demolition waste (CDW) is generated by the different activities of the construction sector at high rates. The sectoral research conducted by the Brazilian Association for Recycling of CDW (ABRECON) showed values of 84 million cubic meters of CDW generated in Brazil in 2015. The history of CDW recycling in Brazil made progress in 2002, when the National Environment Council of Brazil established Resolution CONAMA 307/02 to regularize the final destination and the possibility of recycling the CDW. In 2010, the National Solid Waste Policy (PNRS) was created that predicts that recycling and reuse of solid waste should be carried out. Thus, CDW recycling is an important activity that depends on the implementation and operation of recycling plants. However, after 2013 there was no increase in the rates of implementation of new CDW recycling plants in Brazil, not even in the state of Rio Grande do Sul. Considering that the financial aspects are fundamental for the operation and new implantations of CDW recycling plants, this work was carried out with the objective of determining and analyzing the main factors influencing financial aspects for the implantation and operation of small CDW recycling plants (50 T / h) and medium size recycling plants (75 t / h), private initiatives. For this, technical visits were made to CDW recycling plants in the city of São Leopoldo, Rio Grande do Sul and Grajaú, São Paulo. In addition, through market research with suppliers and manufacturers, the costs of implementing, operating and maintaining CDW recycling plants of small (50 t / h) and medium size (75 t / h) were determined. With the costs data, a financial analysis was performed by calculating the revenue forecasts and the expenditure forecasts, as well as the payback calculations. To do so, three scenarios were developed which considered: C1) No revenue on the receipt of CDW and production of 100% capacity; C2) With revenue on receipt of CDW and operation of 50% capacity and C3) With revenue on receipt of CDW and 100% capacity operation. The analysis of the financial results showed as factors that influence the financial aspects of CDW recycling plants: production capacity, amount of CDW received, sale of RA, and public management of CDW. The implementation costs represent about 30% of the total costs, the operation costs considering a period of ten years represent 68% of the costs and the maintenance costs 2% of the costs, for both size of plants. The medium-sized plant presented better financial results and lower payback in relation to the small plant, in all scenarios. Among the three scenarios, the C3 presented more favorable financial results and payback. Between scenarios C1 and C2, C2 presented more interesting financial results and payback.
Keywords: Resíduos de construção e demolição; Usinas de reciclagem; Análise financeira; Construction and demolition waste; Recycling plants; Financial analysis; ACCNPQ::Engenharias::Engenharia Civil